Leading remote teams : skills and tools for building influence and impact. (O'Reilly Media, Inc., 2023)
With more teams working remotely, leaders must maintain high team performance with less visibility and supervision. They must inspire and motivate, but from and across time zones. Remote leadership thus poses special challenges and requires adapting traditional skill sets to this new way of working. Those with a better understanding of these challenges and how to surmount them will be more productive and lead more cohesive, successful teams. What you'll learn and how you can apply it Adopt the appropriate leadership mindset and approach to lead a team remotely Develop the skills needed to be a remote leader Build an efficient remote team culture Understand which tools are needed to perform the remote leader's role effectively This course is for you because... You're managing a team of people who work remotely. You're looking to move into a new role where you will manage remote workers. You want to become more proficient at managing remote team members.